KONFLIK SOSIAL ANTARA WARGA KELURAHAN DARA DAN KELURAHAN TANJUNG KECAMATAN RASANA’E BARAT KOTA BIMA - Mansyur; Hermansyah; Sudirman; Anas Djumati (SOKO GURU: Jurnal Ilmu Pendidikan, 2021)
The study aims at discovering the causing factors of social conflict between the people in Dara village in Tanjung village of west Rasana’e subdistrict in Bima city, and the efforts of solution of social conflict between the people in Dara villag in Tanjung village of west rasana’e subdistrict in Bima city. The type of of this study is destriptive qualitative with a case study approach. The determination of the informant was conducted by employing descriptive qualitative sampling technique. Data were collected by employing descriptive qualitative conducted in several stages, namely data reduction, data presentation, and conclusion. The results of the study reveal that (i) the causes of social conflict between the people in Dara village in Tanjung village of west Rasana’e subdistrict in Bima city are: firs, conflict of high school students of SMA Muhammadiah among SMA PGRI in Bima city, the youth, and the ethnic of the village. Second, bullyng between the teenagers of Dara and teenagers of Tanjung in Football Match in Mangge Maci Field Court, (ii) the efforts of solution of social conflict between the people of Dara village and Tanjung village of west Rasana’e subdirsct in Bima city were the prominent religious figure, peominent people, customs figures, Kapolres Bima city, Mayor of Bima the head of Karang Taruna, and the Head of the village.